Changes of the epidemiology and the clinical picture of tularemia in Southern Moravia (the Czech Republic) during the period 1936-1999 - Cerný, Z (European journal of epidemiology, 2001)
The author has processed data on early occurrence of tularemia in Southern Moravia collected from literature, materials of epidemical ward of the Regional Hygienic Station (RHS), Brno, and clinical documentation of patients treated for tularemia at the Clinic of infectious diseases, Brno. Tularemia has been appearing in Southern Moravia since autumn 1936. At that time, 290 people contracted the external (mainly ulceroglandular) form of this disease by handling tularemic hares. During the 60s, large severe epidemics of professionally-acquired pulmonary forms of tularemia, mainly in workers in 'cold divisions' of sugar factories, were occurring. The 25-year period of low occurrence of disease, which followed, was interrupted in 1978 with the curious epidemic of tularemia contracted through the alimentary tract in an old people's home. The transmission medium of the infectious agent was juice which had been made from fallen apples infected by little mouse rodents. In autumn 1994, the number of tularemia cases rose again and, during the season of 1998-1999, 115 cases of tularemia contracted mainly by handling tularemic hares were recorded. The author demonstrated the relationship among sources and modes of transmission of Francisella tularensis and clinical form of the disease using the group of patients treated at the Clinic of infectious diseases in Brno.
Keywords: tularemie; longitudinální studie; Animals; Česká republika; Tularemia; Rabbits; epidemický výskyt choroby; lidé; králíci; zvířata; Disease Outbreaks; Czech Republic; Longitudinal Studies; Humans